P9 The utility of p16 fish in differentiating malignant mesothelioma and benign mesothelial proliferations. (15th November 2016) - Chaturvedi, A; Holme, J; Shah, R; Taylor, P; Evison, M
Abstract : Introduction: One of the commonest genetic abnormalities in malignant mesothelioma is deletion of the 9p21 locus which harbours the p16/CDKN2A gene. Homozygous deletion of p16/CDKN2A can be identified with Fluorescence in situ hybridization (FISH) and may be a useful diagnostic tool where there is difficulty separating malignant from benign mesothelial cell proliferations, e.g. where a lack of invasion into adipose tissue prevents a confident diagnosis of mesothelioma. Methods: The University Hospital of South Manchester is a regional mesothelioma centre in the North West of England. p16 FISH has been in clinical use since 2013 for cases of abnormal mesothelial cell proliferation without conclusive evidence of malignancy. This retrospective study analysed the diagnostic performance of p16 FISH using clinical follow-up and post-mortem studies to clarify final diagnoses. Results: 75 pathological samples underwent p16 FISH analysis 2013–2015; 16 cytology samples (14 pleural fluid, 2 ascitic fluid), 36 VATS pleural biopsies, 16 local anaesthetic thoracoscopy pleural biopsies and 7 percutaneous pleural biopsies. There was one failed test. A final diagnosis based on subsequent definitive pathological sampling, definitive radiological surveillance or post-mortem findings were available for 99% of patient (74/75). 71 patients were ultimately proven to have mesothelioma (39 epithelioid, 13 sarcomatoid, 7 biphasic and 12 NOS), 2 patients were diagnosed benign pleural disease and 1 with metastatic lung cancer. The diagnostic performance of p16 FISH was as follows: sensitivity 69%, specificity 100%, positive predictive value 100%, negative predictive value 8%, and diagnostic accuracy 69%. All positive p16 FISH results were in cases of mesothelioma. The sensitivity of p16 according to specimen type was as follows: fluid cytology 88%, VATS 59%, medical thoracoscopy 57% and percutaneous biopsy 50%. The sensitivity as per histological subtype for p16 FISH was 66% in epithelioid mesothelioma and 73% in sarcomatoid mesothelioma. Discussion: p16 FISH is a useful diagnostic tool to confirm cases of suspected malignant mesothelioma. A positive result is consistent with mesothelioma but a negative result does not exclude it. This data shows promising diagnostic yield in fluid cytology which may be especially relevant in those patients unsuitable for invasive biopsies due to technical or clinical reasons.